(untitled) (European Journal of Interdisciplinary Research and Development, 2023)
This research aims to prepare skillful physical exercises using the circuit training method to develop some physical attributes and basic skills in tennis. The researcher followed the experimental design due to its suitability with the problem in question; research sample was chosen in the intentional way (purposefully). They are 12 players of Al- Sayd Sports Club who were divided into two equal, experimental and control groups. As soon as the main experiment was performed and tests were conducted, SPSS was used to process the data statistically. Results showed that in the post-tests, the experimental groups scored higher in some physical attributes and basic skills under study than the control group. It is recommended that all coaches should use physical and skill exercises in a circular training manner because of their great and rapid role in developing some physical characteristics and basic skills in tennis due to the diversity of exercises within the training unit and their pairing (physical, skillful) and controlling the players in terms of number and times, performance and rest during group training.